The economic impact of inventory credit programme (ICP) on cereal farmers in the PRU District of the Brong Ahafo Region - Adjei, Theophilus (2011)
A Thesis submitted to the Department of Banking and Finance, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Executive MBA, 2008